PENINGKATAN PEMBERDAYAAN MASYARAKAT BERBASIS EDUKASI DALAM PENGENDALIAN DIABETES MELITUS - Afif Kurniawan; Rukmini Rukmini; Silvia Haniwijaya Tjokro; Novita Fajriyah (Community Development in Health Journal, 2026)
Introduction & Aim: Diabetes mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin secretion, insulin action, or both. Many health problems are found in communities with a history of diabetes mellitus sufferers, so an effective approach is needed to face this challenge through programs that will be implemented, which are expected to have an impact on improving the quality of public health. The purpose of this activity is to increase knowledge, awareness, and encourage the community to be aware and participate in diabetes prevention. Method of Activity: This activity was carried out in RT 2 and RT 5, Kapasan sub-district, targeting 30 elderly people. The steps of the activity were preparing booklets, coordinating with residents, administering pretest questionnaires, followed by providing education, games, and posttests. Results: The average test score of the elderly in RT 02 increased from 72 to 86 points. In RT 05, the average test score increased from 58 to 74. With p-values ​​of 0.045 and 0.003, respectively. Discussion: The majority of respondents who previously had limited understanding became more aware of healthy eating patterns, physical activity, and the importance of blood sugar checks. However, the insignificant change in attitudes suggests that despite increased knowledge, attitude formation requires a longer process. Attitudes are related to long-established values ​​and beliefs, particularly in the adult and elderly age groups. Therefore, increased knowledge has not been fully accompanied by strong changes in attitudes.